A fracture-propagation-control model for pipelines transporting CO2-rich mixtures including a new method for material-model calibration. (15th July 2017) - Nordhagen, H.O.; Munkejord, S.T.; Hammer, M.; Gruben, G.; Fourmeau, M.; Dumoulin, S.
Highlights: We consider fracture-propagation control in pipelines transporting CO2 -rich mixtures. The fluid and structure models are physically based and fully coupled. We present a new material-model calibration method using available data as input. Good agreement is found with three published medium-scale crack-arrest experiments. We discuss the stress state ahead of the crack tip. Abstract: This work considers a predictive numerical modelling approach for fracture-propagation control in CO 2 -transport pipelines, an area where current engineering tools do not work. Fluid–structure interaction model simulations are compared with three published medium-scale crack-arrest experiments with CO 2 -rich mixtures. The fluid flow is calculated by a one-dimensional homogeneous equilibrium model, and the thermodynamic properties of CO 2 are modelled using the Span–Wagner and the Peng–Robinson equation of state. The pipe material is represented by a finite-element model taking into account large deformations and fracture propagation. Material data commonly found in the literature for steel pipes in crack-arrest experiments is not sufficient to directly calibrate the material model used here. A novel three-step calibration procedure is proposed to fill the information gap in the material data. The resulting material model is based on J 2 plasticity and a phenomenological ductile fracture criterion. It is shown that the numerical model provides good predictions of the pressure along the pipe, the ductile fracture speed and a conservative estimate of the final crack length. An approximately plane-strain stress state ahead of crack tip implies that a fracture criterion accounting for a wide range of stress states is not necessary.